Collective synthesis of 4-Hydroxy-2-pyridone alkaloids and their antiproliferation activities - Ding, Feiqing (2014)
A collective synthesis of 4-hydroxy-2-pyridone alkaloids—specifically, pretenellin B, prebassianin B, farinosone A, militarione D, pyridovericin, and torrubiellone C—has been achieved. Key steps include using a strategic convergent method to synthesize the densely substituted pyridone key intermediate by Suzuki–Miyaura cross-coupling reaction, a divergent synthesis approach of target molecules by aldol condensation of pyridone intermediate with homologous aldehydes, and an iterative synthesis of homologous aldehydes with all-trans-polyene backbones. Interestingly, among the six tumor cell lines investigated, torrubiellone C was found to induce potent and apoptotic inhibitory activities on Jurkat T cells with IC50 values of 7.05 μm. Hence, this approach could potentially contribute to the synthesis of bioactive small-molecule libraries as well as drug discovery.